2023
DOI: 10.20471/dec.2023.59.02.07
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Clinical and Metabolic Variables and Smoking among Antipsychotic- Naïve First-Episode and Nonadherent Chronic Patients with Psychosis

Abstract: An interaction between smoking and antipsychotic medications could potentially affect treatment efficacy and promote metabolic side effects. We investigated the contribution of smoking status towards Positive and Negative Syndrome Scale (PANSS) scores and metabolic syndrome- related parameters (plasma lipid and glucose concentrations, and body mass index) among two groups of unmedicated patients with psychosis from the Croatian population: antipsychotic-naïve first-episode patients and nonadherent chronic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Although this study did not differentiate between smoking and non-smoking patients, previous studies showed that smokers exhibited a greater frequency of metabolic syndrome and had distinct factors contributing to metabolic syndrome than non-smokers [16,17]. Also, this study did not differentiate between medicated and unmedicated patients.…”
Section: Discussionmentioning
confidence: 70%
“…Although this study did not differentiate between smoking and non-smoking patients, previous studies showed that smokers exhibited a greater frequency of metabolic syndrome and had distinct factors contributing to metabolic syndrome than non-smokers [16,17]. Also, this study did not differentiate between medicated and unmedicated patients.…”
Section: Discussionmentioning
confidence: 70%